PENGARUH KEMAJUAN TEKNOLOGI INFORMASI, PENGETAHUAN INVESTASI DAN UANG SAKU MAHASISWA TERHADAP MINAT INVESTASI DI PASAR MODAL SEBAGAI SARANA INVESTASI BAGI KALANGAN MUDA - Faradilla Sari; Ayuni Fitri; Irma Susanti (Jurnal Ekonomi Sakti, 2022)
The number of millennials or generations born between 1981-2000 according to the 2017 Susenas (National Socio-Economic Survey) reached 88 million people or 33.75 percent of the total population of Indonesia (BPS). PT Kustodian Sentral Efek Indonesia (KSEI) noted that young people or the millennial generation still dominates the number of investors in the Indonesian capital market. This study aims to find out and see to what extent young people are interested in investing in the Indonesian capital market and see what makes young people still lack interest in investing in the Indonesian capital market. The population of this research is young people, for example students as students who are highly intellectual and follow the development of technology and the times.